2010
DOI: 10.3109/10582452.2010.483968
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Fibromyalgia Syndrome in Patients with Polycystic Ovary Syndrome

Abstract: Objectives: Polycystic ovary syndrome [PCOS] is one of the most common reproductive abnormalities and is characterized by hyperandrogenemia. We aimed to assess the frequency of fibromyalgia syndrome [FMS] and psychological distress in patients with PCOS. Methods: Forty patients with PCOS and 39 age-matched healthy controls were included in the study as PCOS and healthy normal control [HNC] groups. The diagnosis of FMS was based on the American College of Rheumatology criteria of 1990, and the diagnosis of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A history of polycystic ovarian syndrome, hirsutism, and ovarian cysts were reported more often in patients with CFS compared with controls. Soyupek et al (2010) aimed to assess the association between fibromyalgia syndrome and psychological distress in patients with PCOS. The results concluded that the frequency of FMS as well as anxiety risk was found to be increased in PCOS.…”
Section: /mentioning
confidence: 99%
“…A history of polycystic ovarian syndrome, hirsutism, and ovarian cysts were reported more often in patients with CFS compared with controls. Soyupek et al (2010) aimed to assess the association between fibromyalgia syndrome and psychological distress in patients with PCOS. The results concluded that the frequency of FMS as well as anxiety risk was found to be increased in PCOS.…”
Section: /mentioning
confidence: 99%
“…The relationship between IR and chronic pain has been established [ 104 ], and obesity can also increase the prevalence of chronic pain [ 105 , 106 ]. IR is also associated with fibromyalgia syndrome [ 107 ]; this pathophysiology was reported in a population of patients with PCOS who exhibited an increased frequency of fibromyalgia [ 108 ], which is a widespread pain anomaly characterized by a decreased pain threshold. A patient with fibromyalgia may experience musculoskeletal pain accompanied by an increased frequency of disorders pertaining to sleep, fatigue, mood, and memory.…”
Section: Potential Exacerbating Factors For Pain In Patients With Pcosmentioning
confidence: 99%